Tetramerization of STAT5 regulates monocyte differentiation and the dextran sulfate sodium-induced colitis in mice - Monaghan, Kelly L.; Zheng, Wen; Akhter, Halima; Wang, Lei; Ammer, Amanda G.; Li, Peng; Lin, Jian-Xin; Hu, Gangqing; Leonard, Warren J.; Wan, Edwin C. K. (Frontiers in Immunology, 2023)
In response to external stimuli during immune responses, monocytes can have multifaceted roles such as pathogen clearance and tissue repair. However, aberrant control of monocyte activation can result in chronic inflammation and subsequent tissue damage. Granulocyte-macrophage colony-stimulating factor (GM-CSF) induces monocyte differentiation into a heterogenous population of monocyte-derived dendritic cells (moDCs) and macrophages. However, the downstream molecular signals that dictate the differentiation of monocytes under pathological conditions is incompletely understood. We report here that the GM-CSF-induced STAT5 tetramerization is a critical determinate of monocyte fate and function. Monocytes require STAT5 tetramers to differentiate into moDCs. Conversely, the absence of STAT5 tetramers results in a switch to a functionally distinct monocyte-derived macrophage population. In the dextran sulfate sodium (DSS) model of colitis, STAT5 tetramer-deficient monocytes exacerbate disease severity. Mechanistically, GM-CSF signaling in STAT5 tetramer-deficient monocytes results in the overexpression of arginase I and a reduction in nitric oxide synthesis following stimulation with lipopolysaccharide. Correspondingly, the inhibition of arginase I activity and sustained supplementation of nitric oxide ameliorates the worsened colitis in STAT5 tetramer-deficient mice. This study suggests that STAT5 tetramers protect against severe intestinal inflammation through the regulation of arginine metabolism.